2023
DOI: 10.1093/nar/gkad176
|View full text |Cite
|
Sign up to set email alerts
|

Insights into translocation mechanism and ribosome evolution from cryo-EM structures of translocation intermediates of Giardia intestinalis

Abstract: Giardia intestinalis is a protozoan parasite that causes diarrhea in humans. Using single-particle cryo-electron microscopy, we have determined high-resolution structures of six naturally populated translocation intermediates, from ribosomes isolated directly from actively growing Giardia cells. The highly compact and uniquely GC-rich Giardia ribosomes possess eukaryotic rRNAs and ribosomal proteins, but retain some bacterial features. The translocation intermediates, with naturally bound tRNAs and eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The Thr48 residue, located in the switch I region of the GTP binding pocket, is highly conserved and sequence-aligned closely to Thr56 in human eEF2. Additionally, recent time-resolved cryo-EM studies show that switch I undergoes a large flipping motion (12, 13, 26). This motion creates a Pi release channel essential for EF-G’s function on the ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…The Thr48 residue, located in the switch I region of the GTP binding pocket, is highly conserved and sequence-aligned closely to Thr56 in human eEF2. Additionally, recent time-resolved cryo-EM studies show that switch I undergoes a large flipping motion (12, 13, 26). This motion creates a Pi release channel essential for EF-G’s function on the ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…Most eukaryotic ribosomes, monosome, LSU, and SSU sediments, at the 80S, 60S, and 40S, respectively, and possess four rRNA species 28S, 18S, 5.8S and 5S. The high-resolution ribosome structures from other protozoans: Trypanosoma brucei (Hashem et al, 2013), Plasmodium falciparum (Wong et al, 2014), Leishmania donovani (Shalev-Benami et al, 2017), Trichomonas vaginalis and Toxoplasma gondii (Li et al, 2017), Euglena gracilis (Matzov et al, 2020) Giardia lamblia (Hiregange et al, 2022) (Majumdar et al, 2023); Eiler et al 2024) have revealed the species-specific unique features of their architecture and protein synthesis. The atomic details for E. histolytica ribosome architecture are absent as no structure is available.…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution ribosome structures from other protozoans: Trypanosoma brucei 19 , Plasmodium falciparum 20 , Leishmania donovani 21 , Trichomonas vaginalis and Toxoplasma gondii 22 , Euglena gracilis 23 Giardia lamblia 24,25,26 have revealed the speciesspecific unique features of their architecture and protein synthesis. The atomic details for E. histolytica ribosome architecture are absent as no structure is available.…”
Section: Introductionmentioning
confidence: 99%